Combining inhibition of immune checkpoints and PARP: rationale and perspectives in cancer treatment. (2nd November 2022) - Catalano, Martina; Francesco Iannone, Luigi; Cosso, Federica; Generali, Daniele; Mini, Enrico; Roviello, Giandomenico
ABSTRACT: Introduction: Genomic instability resulting from the inability of cells to repair DNA damage is a breeding ground for immune checkpoint inhibitors (ICIs) and targeted treatments. Poly (ADP-ribose) polymerase inhibitors (PARPi) interfere with the efficient repair of DNA single-strand break damage inducing, mainly in tumors with existing defects in double strand DNA repair system, synthetic lethality. Areas covered: By amplifying the DNA damage and inducing immunogenic cell death PARPi leads tumor neoantigens to increase, upregulation of programmed death-ligand 1, and modulation of the tumor microenvironment facilitating a more intense antitumor immune response. In this review, we reported the immunological role of PARPi and the rational use of the combination with ICIs, evaluating data from combination clinical trials and discussing perspectives. Expert opinion: Several prospective combination studies to overcome existing limitations to PARPi and ICI single agents are currently ongoing. The identification of the different resistance mechanisms to PARPi and ICI as well as the development of accurate and predictive biomarkers of response should be a priority to identify the patients who may most benefit from this combination. Similarly, clarifying the role and interaction between the DNA damage repair pathways and the tumor immune microenvironment would increase success of the combination.